Strategi Pemasaran Dalam Meningkatkan Penjualan Produk Samase di Salimah Fashion Sungai Kambang Telanaipura Kota Jambi - M. Rezha Rizqullah Vahlevi Abas; M. Nazori; Ahmad Syukron Prasaja (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this thesis is to determine the Marketing Strategy in Increasing Sales of Samase Products at Salimah Fashion Sungai Kambang Jambi, Telanaipura District, Jambi City. This thesis uses a qualitative approach, the informants in this study are shop owners, shop employees and buyers, using data collection methods through observation, interviews, and documentation. The results of the study show the sharia marketing strategy at the Salimah Fashion Shop, including prioritizing the honesty of the products sold so that consumers do not feel cheated by the products offered, the company also continues to offer discounts and additional bonuses to add information for consumers who want to buy clothes, different offerings, serving better, maintaining the company's image and managing customer complaints. The obstacles faced in marketing and such as information is not up to date and human resources are limited. The solutions taken include openness of information and conducting socialization